2015
DOI: 10.3390/s150202920
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Biomass and Canopy Height in Bermudagrass, Alfalfa, and Wheat Using Ultrasonic, Laser, and Spectral Sensors

Abstract: Non-destructive biomass estimation of vegetation has been performed via remote sensing as well as physical measurements. An effective method for estimating biomass must have accuracy comparable to the accepted standard of destructive removal. Estimation or measurement of height is commonly employed to create a relationship between height and mass. This study examined several types of ground-based mobile sensing strategies for forage biomass estimation. Forage production experiments consisting of alfalfa (Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 39 publications
2
75
1
1
Order By: Relevance
“…This outcome can be explained by the higher difficulty involved in the detection of less tall objects and their modelling due to (a) their closer distance to the soil that increases the difficulty for the SfM software and (b) the taller surrounding grass, especially at the end of the growth period that reduces its visibility in the extreme oblique images. To obtain the DTM needed to build the CHM, it is possible to use a flight without vegetation (Bendig et al, ), interpolation of points (manually or automatically) classified as ground using the borders of the plots or visual bare soil areas (Viljanen et al, ; Yue et al, ), to use a ultrasonic or laser scanner (Pittman et al, ) or interpolating X , Y and Z coordinates of the plot corners measured with a GPS (Chang, Jung, Maeda, & Landivar, ). In our case, very good results were obtained using interpolated coordinates measured with the RTK GPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This outcome can be explained by the higher difficulty involved in the detection of less tall objects and their modelling due to (a) their closer distance to the soil that increases the difficulty for the SfM software and (b) the taller surrounding grass, especially at the end of the growth period that reduces its visibility in the extreme oblique images. To obtain the DTM needed to build the CHM, it is possible to use a flight without vegetation (Bendig et al, ), interpolation of points (manually or automatically) classified as ground using the borders of the plots or visual bare soil areas (Viljanen et al, ; Yue et al, ), to use a ultrasonic or laser scanner (Pittman et al, ) or interpolating X , Y and Z coordinates of the plot corners measured with a GPS (Chang, Jung, Maeda, & Landivar, ). In our case, very good results were obtained using interpolated coordinates measured with the RTK GPS.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to the best of our knowledge, estimation of DMY from canopy height over an entire growing season for perennial ryegrass using high‐resolution UAV‐RGB images has not been reported yet. This is especially challenging as the height of perennial ryegrass canopies are typically lower (0.2 and 0.4 m) than those of other forage crop species such as timothy–meadow fescue mixtures (0.6–0.7 m) (Viljanen et al, ) and bermudagrass/alfalfa mixtures (0.8–1.1 m) (Pittman, Arnall, Interrante, Moffet, & Butler, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the application of sensors in grazed pastures is more difficult than in cut grassland, and there are limitations for each specific sensor technique used for the prediction of sward characteristics (Schellberg et al, 2008;Pullanagari et al, 2012). An effective method for in-field estimation of biomass must reach an accuracy comparable to the accepted standard of destructive procedure (clipping and weighing) (Pittman et al, 2015). Using a data combination of conceptually different sensing methods holds promise for providing more accurate property estimates (Adamchuk et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Farooque et al (2013) developed an integrated automated system comprising an ultrasonic sensor, a digital color camera, a slope sensor and a global positioning system (GPS) to measure plant height, fruit yield, slope and elevation in wild blueberry fields and concluded the developed system was accurate, reliable and efficient to map such characteristics in real-time kinematics (RTK). Pittman et al (2015) examined several types of ground-based mobile-sensing strategies (ultrasonic, laser and spectral sensors) to estimate biomass and canopy height in Bermuda grass, alfalfa and wheat. They suggested that using mobile-sensor-based biomass estimation methods could be an effective alternative to the traditional clipping method for a rapid and accurate in-field biomass estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, acoustic spectrum in a wide frequency range were applied, and the quality of the ultrasonic signals are significantly improved [37] , which may promote its application. To improve measurement accuracy, ultrasonic sensors can be also combined with lidars [38] .…”
Section: Plant Height Measurementsmentioning
confidence: 99%